Pengenalan Pembelajaran Komputer Anak Usia Dini - Netti Herawati (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
In this study, computer learning for young children in TK Muslimat Nahdatul Ulama Kota Palembang is described. The study takes a qualitative approach while using the descriptive method. The study's informants were computer teachers. In order to collect data for this study, observational methods, interview methods, and documentation methods were used. Data triangulation techniques are utilized for data analysis. Children's computer education at TK Muslimat Nahdatul Ulama Kota Palembang has produced successful results. Children are offered computer learning materials by their teachers, which progress from the easiest to the most challenging. To make it easier for kids to acquire computer information, teachers employ a variety of computer learning techniques, including cooperative ways, tutorial methods, demonstration methods, training methods and practice, and game-based learning. In its implementation, there are still obstacles faced by children’s, teachers, and computers used.